THE RELATIONSHIP BETWEEN PENGELOLAAN OBAT AND THE QUALITY OF HEALTH SERVICES AND ITS IMPACT ON THE PERFORMANCE OF XYZ DISTRIC HOSPITAL - Liska Marlindasari; MGS Aritonang; Tedy Herdiana (Borneo Journal of Pharmascientech, 2020)
The implementation of Jaminan Kesehatan Nasional (JKN, National Health Insurance) program has increased drug demand. However, a lack of inventory is known to have caused drug stock-out that affected hospital performance. In this descriptive analytic study a cross sectional approach was used and 100 patients were taken as a random sample. Primary data were obtained through structured questionnaire interviews and analyzed using multiple logistic regression tests. In general, the results of the study showed: 36.8% of respondents thought that the quality of Pengelolaan Obat was not good, 36.0% were doubtful about the quality of health services, and 41.0% agreed that the performance of XYZ District Hospital was good. Pearson’s correlation test results showed there was a relationship between Pengelolaan Obat and service quality (p <0.05, 95% CI) with procurement as the most dominant indicator (B = 1.343). In addition, there is a relationship between service quality and performance (p <0.05, 95% CI), with physical evidence as the most dominant indicator (B = 1.299) and between Pengelolaan Obat and performance (p <0.05, 95% CI ), with internal business (B = 1,239) and customers (B = 1,012) as the most dominant factor.